Developmental changes in KCC1, KCC2, and NKCC1 mRNA expressions in the rat brain - Wang, Cong; Shimizu-Okabe, Chigusa; Watanabe, Kazuo; Okabe, Akihito; Matsuzaki, Hideo; Ogawa, Tsuguhiro; Mori, Norio; Fukuda, Atsuo; Sato, Kohji (Brain research. Developmental brain research, 2002)
We investigated the expressions of KCC1, KCC2 and NKCC1 mRNAs in the developing rat brain. The neuroepithelium showed abundant KCC1 and NKCC1 mRNA expressions, while KCC2 mRNA was not detected there. In contrast, KCC2 mRNA was preferentially expressed in postmitotic mature neurons. These results suggest that the appearance of KCC2 expression mainly depends on the maturation of individual neurons.